2010
DOI: 10.1103/physrevlett.104.119603
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Imaging of the Hydrogen Subsurface Site in RutileTiO2

Abstract: The adsorption of hydrogen on oxides leading to the formation of OH species and the subsurface diffusion of H atoms are topics of pronounced interest with regard to understanding oxide surface chemistry. In a recent Letter by Enevoldsen et al. [1], the authors use ab initio density functional theory (DFT) calculations to determine the activation energy for subsurface diffusion of H atoms. The value obtained by them, 2.4 eV, is rather high and would imply that this process can be basically neglected at room tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…However, the higher barrier (1.00 eV) makes this process less likely to occur compared to other terminations. The value of 1.00 eV is consistent with the previous reports (1.11 eV [13], 0.93 eV [47]). The small difference can come from the different coverage, layers and sizes, and the use of GGA+U in the present work.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…However, the higher barrier (1.00 eV) makes this process less likely to occur compared to other terminations. The value of 1.00 eV is consistent with the previous reports (1.11 eV [13], 0.93 eV [47]). The small difference can come from the different coverage, layers and sizes, and the use of GGA+U in the present work.…”
Section: Methodssupporting
confidence: 92%
“…In this process, the calculated ∆E is -0.08 eV, and the activation barrier of H migration is 0.79 eV, indicating that H diffusion to the subsurface region is an activated process, thermodynamically slightly favorable. For (110) it was shown previously that the direct migration O2C to subsurface was more energetic [47]. Fig.…”
Section: Methodsmentioning
confidence: 71%
“…[4,5] Finally, in a recent paper by Yin et al [6] it has been found that heating of a hydroxylated single crystal TiO 2 (110) substrate does not lead to the expected desorption of H 2 or H 2 O molecules, but instead to a diffusion of H atoms into the bulk of the crystal. [7] In theoretical calculations this surprising behaviour was rationalized by the large activation energy of 2.52 eV for recombination of H atoms to form dihydrogen at the TiO 2 surface. This value considerably exceeds that for diffusion into the bulk, for which an activation energy of 1.1 eV has been reported.…”
Section: Heshmat Noeimentioning
confidence: 96%
“…This value considerably exceeds that for diffusion into the bulk, for which an activation energy of 1.1 eV has been reported. [6][7][8] Recently published STM images have provided direct evidence for the population of such subsurface sites by H atoms on TiO 2 substrates. [9] In case of ZnO single crystal surfaces it has been recently demonstrated that exposure of the mixed-terminated ZnO(10 " 10) to atomic hydrogen leads to the metallization of the surface, [10] whereas exposure of the oxygen-terminated OZnO(000 " 1) surface leads to the occupation of bulk interstitial sites.…”
Section: Heshmat Noeimentioning
confidence: 99%
“…It is well known that the surface properties strongly vary with different crystallographic orientations, which can greatly affect their reactivity [42,43,44,45,46]. For rutile TiO 2 , the main exposed low energy surface is the (110) surface, which is also the most studied [23,28,47,48,49,50,51].…”
Section: Introductionmentioning
confidence: 99%